An analysis of high-performing board criteria on Malaysian government-linked companies performance - Wan Izyani Adilah, Wan Mohamad; Mohd Hafiz, Harun; Noryati, Yaakub; Wan Amalina, Wan Abdullah@Wan Abdullah (2017)
This paper attempts to examine the relationship between board structure and the financial performance of state-owned GLCs. Five corporate governance variables were examined, namely the board size, the proportion of independent directors, the financial literacy of directors, multiple directorships and the frequency of meetings. A sample of 90 state-owned GLCs in Malaysia was studied using their published annual reports from the financial years of 2008 until 2012. The findings show that all the state-owned GLCs match the criterion of high-performing board. Only board size is significant in determining the financial performance of the state-owned GLCs, and this is probably due to the fact that they are all owned by the state government and are more or less under a similar budget from the federal government. The insignificance of results on the remaining corporate governance variables might be due to the fact that MCCG has been implemented comprehensively in all of the companies.